Avaliação e qualidade no novo Plano Nacional de Educação: avanços e possíveis retrocessos? - Fabiana Alvarenga Filipe; Regiane Helena Bertagna (EccoS – Revista Científica)
This paper examines the new National Education Plan (Law n.º 13 , 005 / 2014 ), emphasizing the aspects that it applies to the external large-scale assessments and to the educational quality. It was established, from the analysis, that the new National Education Plan presents a bias in marketing logics character (based in the neoliberal ideology) relating the education quality with such statistical indicators (as, for example, the Basic Education Development Index – Ideb), restricting the education quality in quantitative results and products, disregarding the processes and expanding the concept of public education with the inclusion of the private sector. The discussions raised by the analyzed law, points to another conception of education quality, the social quality, based on the collective construction (participative) in defense of education as a social right that enables the human emancipation.